EYANG RAMA : MEDIA PEMBELAJARAN WAYANG BERMUATAN NILAI KARAKTER UNTUK SISWA SMP DI YOGYAKARTA - Exwan Andriyan Verrysaputro; Nur Indah Sholikhati; Lely Tri Wijayanti (Universitas Muhammadiyah Mataram, 2022)
Eyang Rama is the name of the learning media product produced in this research and development. Eyang Rama is an acronym for Educational Cartoon Wayang Ramayana. This research is included in the Research & Development research. Research & Development (RnD). The data in this study were collected using questionnaires. Data is obtained from users, namely teachers and students. The analysis is carried out with descriptive qualitative analysis. Based on the collected data, the results of this study are that Eyang Rama was developed through four stages, namely: 1) the analysis stage, the media design stage, the media development stage, and the trial stage; 2) the effectiveness rate of Eyang Rama is 84.2%. The figure is obtained from user ratings, namely teachers 82% and students 86%. This figure shows that this media is effectively used for character-charged wayang learning for junior high school students in Yogyakarta.